Pengaruh Kombinasi Hasil Fermentasi Ampas Tahu Dan Dedak Padi Terhadap Pertumbuhan Biomassa Cacing Sutera (Tubifex Sp) - Mulis; Aldrianto B. Hunow; Sutianto Pratama Suherman (Transbahasa, 2023)
This studyiaims to determini the effectiof the combination of fermented tufo dregs and rice bram on the growth of silkwormibiomass. This researchiwas conductedifrom May to Julyi2022. Theimethod used was am experimental method with a completelyirandomized designi(CRD) with 4 treatments and 3 replications. The treatmentsiin this studyiwere reatment A (Control), B (Combination of 50% tufo dregs and 50% rice bran), C (Combination of 75% tufo dregs and 25% rice bran), D (Combination of 25% tofu dregs and rice bran 75%),Using gutters with a size of i80 cm xi10 cm xi12 cm.i10 grams container, the test materials used were organic tufo dregs and rice bran fermeted with EM4 (Effective Microoganim-4) prebiotic.iThe results of ithe ANOVA testianalysis showed that population growth and silkworm biomass using a combination of tofu dregs fermentation and rice bran had isignificantieffecti(P>0.05) with itheibest resultsiin treatmentiD, which was 7169 induviduals and absolute biomass in D, which was 21,02 (grams) Water iquality iduring the study was in the standard range for silkworm growth.